The Differences Between Tumor Necrosis Factor-Î± (TNF-Î±) Expression in Fleshy and Atrophy Pterygium - Reza Satrio; Winarto Winarto; Siti Sundari (Majalah Oftalmologi Indonesia, 2015)
Background: Pterygium is a conjungtival fibrovascular degenerative process which fleshy type was different to atrophy type, in which post operative recurrencies was high especially fleshy type. The exact pathogenesis were not clearly understood, it was reported that many inflammation mediators had a play role, including Tumor Necrosis Factor-Î± (TNF-Î±). Objective of the study was to revealed a different expression of TNF-Î± in fleshy and atrophy type. Method: Cross-sectional study design have been done with independent variable was TNF-Î± and dependant vaiable was pterygium type. Samples consist of 20 patients fleshy type and 20 patients atrophy type, both groups were given fluorometholone eye drop for 1 week prior surgery to suppress the degree of inflammation. The baseline data was recorded e.g. demography, the size of pterygium, Tear Break Up Time (TBUT), Schirmer test and Ferning test. Pterygium excission followed by limbal stem cell graft, and examination of TNF-Î± expression by immunohistochemistry. TNF-Î± expression was analyzed using 2 x 2 table. Result: Baseline data of both groups were not significantly different, except TBUT (p=0.000) and the clinical characteristic of pterygium (p=0.000). TNF-Î± expression in fleshy type tend to be higher (total Allred score mean 4.70) but not significantly different than atrophic type (total Allred score mean 4.54 and p=0.61). Previous fluorometholone treatment prior to surgery might be suppressed the inflammatory cytokine. Conclusion: No significant difference of the TNF-Î± expressions between fleshy and atrophy type of pterygium. Keywords: pterygium, fleshy type, atrophy type, TNF-Î±, immunohistochemistry